(untitled) (Bangladesh Journal of Scientific and Industrial Research, 2011)
Levels of amino acids were determined in the grains of wheat, Triticim durum Desf. The raw sample was best in Arg, Ile, Leu, Thr, Val, Ala, Asp, Glu and Pro but similar to germinated sample in Lys whereas germinated sample was best in His, Met, Cys, Phe,Gly, Ser and Tyr. The total amino acid contents were; raw 12[74.1 g/100 g crude protein (c. p.)], steeped 63.4 g/100g c. p.) and germinated (70.6 g/100 g c. p.) with respective essential amino acids of 32.9 g/100 g c. p., 30.0 g/100 g c. p. and 32.4 g/100 g c. p. The Predicted Protein Efficiency Ratio (P-PER) levels were 2.46 (raw), 2.27 (steeped) and 2.19 (germinated). Only germinated samples enhanced the quality of the wheat amino acid levels up to the tune of 41.2 %. However, significant differences occurred between raw/steeped and raw/germinated at r = 0.05. Key words: Amino acid; Raw; Steeped; Germinated; Wheat grains DOI: http://dx.doi.org/10.3329/bjsir.v46i1.8112 Bangladesh J. Sci. Ind. Res. 46(1), 89-100, 2011